2015
DOI: 10.1007/s10815-015-0462-x
|View full text |Cite
|
Sign up to set email alerts
|

Can apoptosis and necrosis coexist in ejaculated human spermatozoa during in vitro semen bacterial infection?

Abstract: The cellular death observed in spermatozoa in the presence of inflammatory mediators may be due to both apoptosis and necrosis. Here, we demonstrate for the first time that direct contact of conditionally pathogenic bacteria with ejaculated human sperm may play an even greater role in the promotion of apoptosis than in case of some pathogenic bacterial strains. These findings suggest that significant bacteriospermia and leukocytospermia may be direct causes of subfertility or additional negative factors worsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 47 publications
(59 reference statements)
1
21
0
2
Order By: Relevance
“…In another experimental study, the loss of sperm motility induced by the soluble products of E. coli was accompanied by the increased intrinsic mitochondrial generation of ROS and membrane lipid peroxidation [8]. In line with these findings, our original experimental data have demonstrated a direct role for conditionally pathogenic bacterial strains, S. haemolyticus and B. ureolyticus, in the induction of sperm apoptosis, as reflected by reductions in sperm motility, mitochondrial depolarization, lipid peroxidation, loss of sperm membrane asymmetry, PS externalization, and DNA fragmentation with subsequently reduced competence of sperm-oocyte fusion [9,31]. All the above data have provided molecular evidence for the induction of sperm death by distinct bacterial agents (differing in pathogenicity and metabolism), partially due to intrinsic apoptotic cascade.…”
Section: Apoptosis/necrosismentioning
confidence: 57%
See 3 more Smart Citations
“…In another experimental study, the loss of sperm motility induced by the soluble products of E. coli was accompanied by the increased intrinsic mitochondrial generation of ROS and membrane lipid peroxidation [8]. In line with these findings, our original experimental data have demonstrated a direct role for conditionally pathogenic bacterial strains, S. haemolyticus and B. ureolyticus, in the induction of sperm apoptosis, as reflected by reductions in sperm motility, mitochondrial depolarization, lipid peroxidation, loss of sperm membrane asymmetry, PS externalization, and DNA fragmentation with subsequently reduced competence of sperm-oocyte fusion [9,31]. All the above data have provided molecular evidence for the induction of sperm death by distinct bacterial agents (differing in pathogenicity and metabolism), partially due to intrinsic apoptotic cascade.…”
Section: Apoptosis/necrosismentioning
confidence: 57%
“…Our data have demonstrated that, during experimental semen infection in vitro, ejaculated human spermatozoa exhibited reduced viability visible in HOS tests and increased proportions of dead sperm [9]. However, DNA fragmentation was observed in both apoptotic and necrotic sperm, and the most part of the latter [31]. This is in agreement with the ultrastructural findings of Collodel et al [110], who observed a high percentage of sperm with anomalies typical of apoptosis, as well as of necrosis, from individuals affected by urogenital bacterial infection, although the percentage of necrotic sperm was predominant in the majority of infected semen samples.…”
Section: Apoptosis/necrosismentioning
confidence: 61%
See 2 more Smart Citations
“…The question then remains what are the underlying pathophysiological mechanisms that result in reduced semen parameters and (in the worst‐case scenario) give rise to infertility. Some authors concentrate only on the induction of necrosis and apoptosis (Fraczek et al ., ), while others propose the putative role of antigenic mimicry that may exist between certain components of spermatozoa and bacterial proteins (Moretti et al ., ). Although thus far such cross‐reaction has been proved only for the flagella of spermatozoa by Moretti et al .…”
Section: Discussionmentioning
confidence: 99%